Investigation of the structure and proteolytic activity of papain in aqueous miscible organic media - Llerena Suster, Carlos Rafael (2012)
The stability of papain was studied in aqueous–organic mixtures by means of residual proteolytic activity along with various spectroscopic analyses (fluorescence and ATR-FTIR combined with isotopic exchange with D2O). The investigated systems contained 1 or 10% (v/v) of an aqueous buffered solution (pH 8.0) in acetonitrile (ACN), methanol (MeOH) or dimethyl formamide (DMF). The results evidenced that papain retained almost all its catalytic activity after 24 h of incubation in the presence of ACN, and a more compact conformation of the enzyme was detected. Papain suffered an important loss of enzymatic activity (ca. 80%) after 24 h incubation in MeOH although, no global conformational change and minor secondary structure rearrangements were detected. This observation suggests that somehow the active site region was altered. On the other hand, papain suffered a complete inactivation when exposed to those media containing DMF. Fluorescence analyses revealed that an irreversible conformational change took place after 24 h incubation, and a moderate increase in b-sheet and b-turn structures was the most relevant finding when secondary structure was analyzed. The evidences demonstrated that the organic solvents induce a more rigid and compact structure of papain regardless of the organic:buffer ratio investigated. In turn, these modifications affect the active catalytic site in the particular case of MeOH and DMF. These findings were in agreement with the thermo-stability of the enzyme performed after heating at 353 K in all the studied media, that is the presence of ACN did not substantially affect the secondary structure of papain. Nevertheless, the a-helix domain demonstrated to be less thermally stable than the b-sheet domain, turning into aggregated structures after heating, especially in the presence of MeOH and DMF.